The SET and ERITME indices: Integrative tools for the management of polluted sites. (June 2015) - Pauget, Benjamin; de Vaufleury, Annette
Highlights: The Sum of Excess of Transfer (SET) index has been improved to consider 8 more metals. Internal concentration of reference (CIRef) for snails is now available for 14 metals. New methodology to evaluate the risk of the transferred metal elements (ERITME). ERITME is an integrative tool that can be used for polluted site management. Abstract: To address the lack of biological methods for assessing soil quality and its contaminant retention capacity and to provide a tool with which stakeholders can assess the risk of transfer of trace elements in the soil to the soil fauna, the Sum of the Excess of Transfers (SET) index from soil to the snail Cantareus aspersus has been broadened to include the internal concentrations of reference (CIRef) for 14 metals and metalloids (As, Cd, Co, Cu, Cr, Hg, Mo, Ni, Pb, Sb, Sn, Sr, Tl and Zn). Weighting the transfer of these elements by a risk coefficient (i.e., their toxicity point) provides a new assessment tool for stakeholders: the ERITME (Evaluation of the Risk of the Transferred Metal Elements) tool. This upgraded tool has been used to highlight unsuspected risks and revise management priorities at an industrial site. Moreover, using the tool to determine the risk from metal trace elements allows for improved environmental risk assessment, as ERITME is an integrative tool based on the real bioavailability of metals rather than chemical measures that often lead to unsatisfactory assessments of transfer. The SET and ERITME integrative tools, using snails as indicators of trace element zooavailability, can be used in environmental risk assessment.